A Review on Kashyapokta Sama Jwara in Children with respect to Viral Fever (AYUSHDHARA, 2024)
"Jwara" is important and critical among all the diseases, because it affects each and every living being. Hence, it has been given first place in the classical texts of Ayurveda. In Ayurveda, Jwara is not merely the concept of raised body temperature, but as is said in Charaka Samhita, 'Deha- Indriya- Manah- Santap' is the cardinal symptoms of Jwara. This can be defined as the state where the body, mind as well as sense organs suffer due to the high temperature. Acharya Kashypa in Vishamjawar chapter explained Sama Jwara. He is only author who explained Sama Jwara. Sama Jwara is characterized by Alpahetu, Bahirmarga, vaikruta, Nirupadrava, ekashraya Laghupaka and Sukhasadhya. Materials and Methods: This study is based on literately review of classical information, published research work and modern literature. The possible correlation has been made between collected information and has been presented in systemic way. Discussion and conclusion: Sama Jwara is explained only by Kashyapa, Lakshanas of which is similar to Bahirvegi Jwara, Rasa dhatugat Jwara, in modern era it can be compared with viral fever.